2018
DOI: 10.1161/circresaha.117.312082
|View full text |Cite
|
Sign up to set email alerts
|

Desmin Phosphorylation Triggers Preamyloid Oligomers Formation and Myocyte Dysfunction in Acquired Heart Failure

Abstract: Ser31 phosphorylated desmin is a likely candidate seed for the nucleation process leading to cardiac PAOs deposition. Desmin post-translational processing and misfolding constitute a new, attractive avenue for the diagnosis and treatment of the cardiac accumulation of toxic PAOs that can now be measured by positron emission tomography in acquired HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
63
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(73 citation statements)
references
References 36 publications
7
63
0
3
Order By: Relevance
“…The presence of insoluble tetramers may be explained by an inefficient desmin assembling leading to the collapse and aggregation of filaments [44]. It is well established that IF are dynamic structures and reversible phosphorylation is a mechanism that plausibly maintains this dynamism affecting its assembling and disassembling [48,49]. In line with this, we found that in Drp/ MC mice desmin was hyperphosphorylated in Ser-31 by a hyperactivated Cdk-1.…”
Section: Discussionsupporting
confidence: 83%
“…The presence of insoluble tetramers may be explained by an inefficient desmin assembling leading to the collapse and aggregation of filaments [44]. It is well established that IF are dynamic structures and reversible phosphorylation is a mechanism that plausibly maintains this dynamism affecting its assembling and disassembling [48,49]. In line with this, we found that in Drp/ MC mice desmin was hyperphosphorylated in Ser-31 by a hyperactivated Cdk-1.…”
Section: Discussionsupporting
confidence: 83%
“…When the heart decompensates, the levels of several contractile proteins decrease while the cell ultrastructure become disorganized. Since this study, many groups, including our groups, reported higher desmin levels in different forms of cardiac disease [22][23][24]34,35]. A higher levels of intact desmin could be either due to an increase in its expression or a decreased ability of muscle cells to dismantle and efficiently degrade desmin.…”
Section: Desmin and Cardiac Diseasementioning
confidence: 68%
“…In fact, we first reported that the misfolding of wild-type desmin leads to the formation of desmin-positive aggregates in endothelin-1-hypertrophied neonatal rat ventricular myocytes [22]. In addition, we demonstrated the accumulation of desmin-positive preamyloid oligomers (PAOs) and amyloid fibrils similar to those observed in the brain of Alzheimer and Parkinson patients, in small and large animal models of heart failure (HF) and in human tissue specimens, in the absence of genetic mutations [23,24]. More recently, Kedia and colleagues confirmed the amyloidogenic properties of wild-type desmin in skeletal muscle through an in-depth biophysical characterization of the desmin sequence [25].…”
Section: Desmin Loss and Gain Of Function In The Heartmentioning
confidence: 78%
“…3D-E). This might explain the desmin accumulation and aggregate formation in these cardiomyocytes, as desmin hyper-phosphorylation can cause filament disassembly [37][38][39][40] and aggregate formation that could also affect the normal turnover of the protein. ; n.s.…”
Section: Alterations In Desmin Protein Levels and Post-translational mentioning
confidence: 99%
“…Normal phosphorylation levels of desmin control the dynamic assemblydisassembly of desmin filaments and potentially regulation of association with its binding partners [37]. On the other hand, desmin hyper-phoshorylation has been proposed as a mechanism of desmin filament disassembly and aggregate formation in cardiac disease [37][38][39][40]. Thus, we can speculate that the hyper-phosphorylation of desmin in Lmna H222P/H222P hearts may represent one potential mechanism that contributes to the deregulation of desmin network dynamics leading to desmin accumulation and aggregate formation.…”
Section: Accepted Manuscriptmentioning
confidence: 99%